2002
DOI: 10.1177/088307380201700610
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Bilateral Perisylvian Syndrome Associated With Congenital Constriction Band Syndrome

Abstract: We report a 7-year-old boy with congenital bilateral perisylvian syndrome and congenital constriction band syndrome. The former is a congenital neurologic syndrome characterized by pseudobulbar palsy, mental retardation, epilepsy, and bilateral perisylvian polymicrogyria The latter is a malformative disorder with digital ring constrictions and amputations, probably caused by early amnion rupture resulting in entanglement of fetal parts by amniotic strands. We believe that the combination of these two malfornat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
(1 reference statement)
3
8
0
1
Order By: Relevance
“…Familial, autosomal and X-linked inheritance has been reported. CBPS has been associated with the chromosomal abnormalities and malformations such as arthrogryposis,[1] clubfeet,[1] micrognathia,[1] polydactyly, constriction band syndrome[2] and pituitary hypoplasia. [3] Our case had hypotonia with no pyramidal signs.…”
Section: Discussionmentioning
confidence: 99%
“…Familial, autosomal and X-linked inheritance has been reported. CBPS has been associated with the chromosomal abnormalities and malformations such as arthrogryposis,[1] clubfeet,[1] micrognathia,[1] polydactyly, constriction band syndrome[2] and pituitary hypoplasia. [3] Our case had hypotonia with no pyramidal signs.…”
Section: Discussionmentioning
confidence: 99%
“…Embryonic vascular factors have been implicated in perisylvian PMG with or without limb anomalies in 22q11 microdeletion syndrome [Robin et al, 2006]. Congenital constriction bands with limb deficiencies or AOS are associated with bilateral perisylvian PMG, septo‐optic dysplasia and periventricular leukomalacia [Amor et al, 2000; Yamanouchi et al, 2002; Stevens and Dobyns, 2004; Papadopoulou et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…The postulated mechanisms include cerebral hypoxia/ischemia, injury during neuronal migration and gene mutation, however the exact cause of this syndrome or the timing of the development of the malformation remains unknown. [1][2][3][4] Although the majority of cases of CBPS appear to be sporadic, reports of cases including twins and siblings suggest a genetic predisposition. However, different modes of inheritance including X-linked, autosomal dominant and autosomal recessive from different families have been reported and the mode of transmission remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Barkovich et al reported that patients with bilateral frontal polymicrogyria had more severe motor delay than speech delay, mild mental retardation and lower frequency of seizures, whereas patients with perisylvian polymicrogyria presented more frequently with speech dysfunction. [6] CBPS has been reported to be associated with malformations such as arthrogryposis, [1] clubfeet, [1] micrognathia, [1] polydactyly, constriction band syndrome [3] and pituitary abnormalities. [11,12] Thirteen to thirty-three percent of cases have been reported to be associated with arthrogryposis multiplex congenital, which is characterized by joint contractures from birth.…”
Section: Discussionmentioning
confidence: 99%